DISTINGUISHING THE INDISTINGUISHABLE OF THE WORDS INJURED, WOUNDED, AND HURT: A CORPUS INVESTIGATION - Dewa Ayu Novi, Kusumawardani (Lingua Scientia, 2017)
Most people, especially EFL students, claimed that English has rich vocabularies. Each vocabulary has many synonyms that could be found in thesaurus. But the problem is, those synonymous words can hardly be differentiated when applied in daily communication. It is because each of the English word has its own context and rule when it is used in a sentence or an utterance. However, in reality, this rule is often ignored by people. It is because they rely more on their intuition. Yet, it needs more than intuition to know the difference and how to use the words properly. The words ‘injured’, ‘wounded’, and ‘hurt’ were chosen as the object of this study, since those words are synonymous and distinguishable. A quick survey had been done by the researcher to know how EFL students and people in general used these three words. It turned out that they used those three words by ignoring the rule and depending on their intuition instead. The aim of this research is to help people to know the difference among those three words. By retrieving data from COCA and finding the collocation of those words, it is hoped that the reader will realize that these synonymous words are not as synonymous as they thought.